SURGICAL TREATMENT OF PATELLAR INSTABILITY IN ADOLESCENT DANCERS. Issue 7 (30th July 2021) - Nunally, KD; Micheli, LJ; Zheng, E; Hussain, Z; Wilson, B; Kocher, M; Yen, YM; Kramer, DE; Heyworth, BE
Background: Adolescent dancers may be a high-risk population for patellofemoral instability (PFI), but the condition remains under-investigated, to date, in this sub-group of athletes. Purpose: The purpose of this study was to (1) investigate the descriptive epidemiology of PFI in adolescent dancers, (2) analyze the efficacy of various patellar stabilization procedures within this population, and (3) compare PFI in dancers to a larger control group of matched, non-dancer athletes. Methods: A retrospective review of athletes, ages 10 to 19, who presented to a single tertiary care center with PFI between 2008 and 2017 was performed. Based on each patient's primary sport, the cohort was divided into a dancer and a non-dancer control group. Demographics, clinical and radiologic features, surgical stabilization technique, and postoperative course and clinical outcomes were collected. Independent categorical groups were tested using chi squared and Fisher exact tests. Results: 258 adolescent athletes were included, 41 of whom were dancers, all females. This group was therefore matched with a control group of similarly aged, all-female athletes with PFI (Table 1 ). 54 athletes had bilateral PFI, yielding 285 knees for analysis. There was no difference between dancer and non-dancer athletes' age, BMI, laterality, mechanism of injury, nor number of preoperative instability events. However, dancers had lower Dejour Classifications (p=0.044), smaller patella inclination angles (20.9±8.14 versus 25.0±9.84; p=0.004), and smaller Caton-Deschamps Indices (1.18±0.161 versus 1.25±0.189; p=0.041). Among dancers, there was no association between surgical stabilization technique and rates of recurrent instability (p=0.418) nor re-stabilization procedures (p=1.0) (Table 2 ). However, dancers who underwent tibial tubercle osteotomy (TTO) had higher rates of subsequent, non-stabilization procedures (66.7%), all for implant removal, compared to those undergoing isolated medial retinacular repairs (MRP) (3.8%) (p<0.001). There was no difference between the dancer and non-dancer athletes' rates of recurrent instability (p=0.297), re-stabilization procedures (p=0.061), nor subsequent non-stabilization procedures (p=0.242). Conclusions: Female dancers with PFI have similar demographic and clinical features as other female athletes with PFI, but have lower rates or less severe trochlear dysplasia, lateral tilt and patella alta. Therefore, the ligamentous laxity inherent in dancers may be a more powerful risk factor for PFI than other non-modifiable risk factors. Notably, the TTO was a powerful stabilization procedure for this sub-population with low rates of recurrent instability episodes and no revision stabilization procedures performed. Rates of implant removal surgery following TTO may be substantial, though this may be technique or surgeon dependent. Tables/Figures: